An endosymbiotic origin of the crimson pigment from the lac insect - Vaishally; Sourajyoti Pal; Kedhar R. Thyagarajan; Shantanu P. Shukla (Proceedings of the National Academy of Sciences, 2025)
Symbioses with microorganisms expand the genetic and metabolic repertoire of many insects. The lac insect Kerria lacca (Hemiptera: Sternorrhyncha) is a phloem-feeding scale insect that is brightly colored due to the presence of natural polyhydroxy-anthraquinone pigments called laccaic acids. The deep red pigments possibly provide defense against pathogens and predators and are commercially important as dyes in textiles, lacquerware, and cosmetics. Laccaic acids are categorized as polyketides comprising an anthraquinone backbone decorated with tyrosine or its derivatives. However, the genetic basis of these pigments remains unknown, as insects are not known to produce aromatic polyketides or tyrosine de novo. Here, we sequence the genome of the lac insect and its two endosymbionts— Wolbachia and a hitherto unidentified, transovarially transmitted yeast-like symbiont (YLS). We found no evidence for the host or Wolbachia to be able to synthesize the pigments. The pigments and their precursors were also not detected in the host plant. Genomic, transcriptomic, and metabolomic analyses combined with fluorescence microscopy identified and characterized YLS as the sole producer of the pigment’s polyketide backbone and tyrosine moiety, demonstrating an endosymbiotic origin of the lac pigments. A nonreducing polyketide synthase gene cluster encoding the laccaic acid backbone was identified. Furthermore, the YLS genome encoded essential amino acids and vitamins that are deficient in the insect’s phloem diet. Experimental fungicide-treated insects exhibited reduced concentrations of laccaic acids and tyrosine, along with decreased body size and weight, indicating a mutualistic association between the lac insect and its YLS.